Emotional valence and contextual affordances flexibly shape approach-avoidance movements - Saraiva, Ana Carolina; Schueuer, Friederike; Bestmann, Sven (Frontiers in Psychology, 2013)
Behaviour is influenced by the emotional content – or valence – of stimuli in our environment. Positive stimuli facilitate approach, whereas negative stimuli facilitate defensive actions such as avoidance (flight) and attack (fight). Facilitation of approach or avoidance movements may also be influenced by whether it is the self that moves relative to a stimulus (self-reference) or the stimulus that moves relative to the self (object-reference), adding flexibility and context-dependence to behaviour. Alternatively, facilitation of approach avoidance movements may happen in a predefined and muscle-specific way, whereby arm flexion is faster to approach positive (e.g. flexing the arm brings a stimulus closer) and arm extension faster to avoid negative stimuli (e.g. extending the arm moves the stimulus away). While this allows for relatively fast responses, it may compromise the flexibility offered by contextual influences. Here we asked under which conditions approach-avoidance actions are influenced by contextual factors (i.e. reference-frame). We manipulated the reference-frame in which actions occurred by asking participants to move a symbolic manikin (representing the self) towards or away from a positive or negative stimulus, and move a stimulus towards or away from the manikin. We also controlled for the type of movements used to approach or avoid in each reference. We show that the reference-frame influences approach-avoidance actions to emotional stimuli, but additionally we find muscle-specificity for negative stimuli in self-reference contexts. We speculate this muscle-specificity may be a fast and adaptive response to threatening stimuli. Our results confirm that approach-avoidance behaviour is flexible and reference-frame dependent, but can be muscle-specific depending on the context and valence of the stimulus. Reference-frame and stimulus-evaluation are key factors in guiding approach-avoidance behaviour towards emotional stimuli in our environment.